2019
DOI: 10.14233/ajchem.2019.22196
|View full text |Cite
|
Sign up to set email alerts
|

Biomethane Production from Anaerobic Codigestion of Palm Oil Mill Effluent with Cattle Manure: A Review

Abstract: Biogas is conventionally utilized in a gas engine to convert the chemical energy into electricity and into thermal energy for heating purposes and is also pumped into the natural gas grid line after impurities are removed. Biogas production from palm oil mill effluent is one of the best options for economic expansion and this would reduce environmental impacts in developing countries like Malaysia. This study aims to perform an analysis of the economic and environmental prospects of biogas production from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 86 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Numerous works on the impact of pH on different parts of a hydrogen-generating process have been conducted, the bulk of which concentrated on the impact of pH during inoculum treatment. Since keeping pH levels between 5 and 6 increased H2 generation and yields, this test began at the optimum pH of 6 [16]. After completion, the pH of NH4Cl experiment significantly decreased from 6 to around 4, whereas the pH of the other experiments increased to about .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous works on the impact of pH on different parts of a hydrogen-generating process have been conducted, the bulk of which concentrated on the impact of pH during inoculum treatment. Since keeping pH levels between 5 and 6 increased H2 generation and yields, this test began at the optimum pH of 6 [16]. After completion, the pH of NH4Cl experiment significantly decreased from 6 to around 4, whereas the pH of the other experiments increased to about .…”
Section: Resultsmentioning
confidence: 99%
“…The loss of VSS was rather substantial while the suspended cell was being used in the hydrogen digester at HRT for 4 h (data not shown). Extreme VSS loss is referred described as "cell wash-out" [16]. Finally, the digester failed due to insufficient VSS maintenance.…”
Section: Resultsmentioning
confidence: 99%
“…The results suggested that as compared to beaker B, the pH adjustment may greatly improve COD removal. pH variations in the biodigester have a substantial effect on numerous parts of the complex bacterial metabolism [23].…”
Section: Resultsmentioning
confidence: 99%